Pengaruh Media Pembelajaran Berbasis PhET Simulation Pada Materi Tekanan Zat Terhadap Keterampilan Berpikir Kritis Siswa SMP - Utami, Meldi Putri; Aristya Putra, Pramudya Dwi; Wahyuni, Diah (Gravity Edu : Jurnal Pembelajaran dan Pengajaran Fisika, 2024)
The purpose of this study was to determine the significant effect of using learning media based on PhET Simulation on substance stress material on junior high school students' critical thinking skills using a quasi-experimental research methodology and a nonequivalent control group design. The subjects of this study were students of class VIIIF and VIIIH of SMPN 3 Jember. The results of the pretest-posttest were used to collect research data, and the parametric independent sample t-test was used to analyze the data. Based on the results of the study, the posttest mean value for the control class was 60.78, while the posttest mean value for the experimental class was 71.28. The mean value of the experimental class is higher than the control class. the mean value in the experimental class is better than the control class. The parametric test using the independent sample t-test found that there was a difference in the average score of the two classes' critical thinking skills with a significance of 0.000. Furthermore, it is strengthened by the right-hand t-test by realizing the value of tcount > ttable. These results determine that the mean score of critical thinking skills in the experimental class is higher than the control class. The difference in the results of critical thinking skills is due to the two classes being treated differently, namely the control class using video experiments and the experimental class using learning media based on PhET Simulation. Based on the research results, it can be concluded that the use of learning media based on PhET Simulation on substance stress material has a significant effect on junior high school students' critical thinking skills.